Bacterial symbionts, Buchnera, and starvation on wing dimorphism in English grain aphid, Sitobion avenae (F.) (Homoptera: Aphididae) - Zhang, Fangmei; Li, Xiangrui; Zhang, Yunhui; Coates, Brad; Zhou, Xuguo “Joe”; Cheng, Dengfa (Frontiers in Physiology, 2015)
Wing dimorphism in aphids can be affected by multiple cues, including both biotic (nutrition, crowding, interspecific interactions, the presence of natural enemies, maternal and transgenerational effects, and alarm pheromone) and abiotic factors (temperature, humidity, and photoperiod). The majority of the phloem-feeding aphids carry Buchnera, an obligate symbiotic proteobacteria. Buchnera has a highly reduced genome size, but encode key enzymes in the tryptophan biosynthetic pathway and is crucial for nutritional balance, development and reproduction in aphids. In this study, we investigated the impact of two nutritional-based biotic factors, symbionts and starvation, on the wing dimorphism in the English grain aphid, Sitobion avenae, a devastating insect pest of cereal crops (e.g., wheat) worldwide. Elimination of Buchnera using the antibiotic rifampicin significantly reduced the formation of winged morphs, body mass and fecundity in S. avenae. Furthermore, the absence of this primary endosymbiont may disrupt the nutrient acquisition in aphids and alter transgenerational phenotypic expression. Similarly, both survival rate and the formation of winged morphs were substantially reduced after neonatal (< 24h old) offspring were starved for a period of time. The combined results shed light on the impact of two nutritional-based biotic factors on the phenotypic plasticity in aphids. A better understanding of the wing dimorphism in aphids will provide the theoretical basis for the prediction and integrated management of these phloem-feeding insect pests.